Soft innovation : economics, product aesthetics, and the creative industries - Stoneman, Paul. (Oxford : Oxford University Press, 2010)
Much of the existing economic literature on innovation has taken a particularly functional viewpoint as to what innovation might be. This book explores 'soft innovation', found in the creative industries such as publishing, film-making, advertising and architecture, which has been hitherto ignored in innovation studies.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Cultural industries -- Technological innovations -- Management; Cultural industries -- Economic aspects; Organizational change